Staging past and present simultaneously: Andrew Bovell's Holy Day (The Red Sea) - Pulford, Donald (Wissenschaftlicher Verlag Trier, 2006)
Andrew Bovell's play, Holy Day (The Red Sea), takes part in Australia's 'history wars,' the ongoing argument concerning the proper relationship between the country's past and its present, particularly regarding the dispossession of the Aborigines and other injustices. While conservatives insist that history is past and we are better served by contemplating the future, others assert that properly moving forward involves a careful consideration of what needs to occur to remedy the injuries of our past. Part of the latter group's case is that the past is ever with us, that then cannot be conveniently annexed from now. Holy Day (The Red Sea) demonstrates this by weaving the present into its depiction of the past. How it does so is the business of this paper.